Evaluation of Amino Acid Profile of Annona muricata (Soursop) Seed Meal Utilization As A Potential Growth Factor and Fish Health Promoter in the Aquaculture Business in Owerri, Southeast, Nigeria - Anyanwu, C.N,; Ogueri, C.,,; Ihem, E.E.,,; Aririguzo, B.N,; Nwaiwu, I.U.O,; Chikaire, J.U,; Okere, P.C,; Ezeafulukwe, C.F,; Madu, H.C,; Okereke-Ejiogu, E.N, (The Bioscan, 2025)
Aquaculture has witnessed remarkable growth in recent decades, driven by increasing demand for fish as a source of protein and the depletion of wild fish stocks. Fish feeds constitutes 40-60% of total cost of aquaculture production, which has made the production of fish highly expensive. Fish meal and soy bean meal have been the primary protein sources in aquaculture feeds due to their excellent nutritional profiles, including well- balanced amino acid composition and high digestibility. However, the competitive nature and rising costs of theses major protein sources have prompted researchers to explore alternative plant-based protein sources. Plant-based proteins offer several advantages such as lower cost, greater availability and potential sustainability for fish feed production. Therefore, attempts are made to cut down the cost of production without actually compromising in the nutritional quality and bioavailability of feed ingredients for fish culture. The first approach towards the research was by gathering the seeds together, and subjecting them into fermentation process technique that lasted for 5 days. This was done to detoxify the A. muricata seeds of some anti- nutritional factors to enhance the nutrient value of the plant seed. The fermented seeds were brought out and air-dried at room temperature of 20-25℃ for 4 days. The air-dried seeds were grounded into powdery form and subjected to Amino Acid Analysis, using the High Performance Liquid Chromatography (HPLC) equipped with a binary pump and UV/Vis detectors. This was followed with a fluorescence detector to separate them into columns for individual amino acid separation and identification. The results revealed a total a total of 18 Amino Acids identified, with Total Amino Acid content of 106.13g/100g Crude Protein, 45.929/100g Total Essential Amino Acids (TEAA) and 60.21 Non-Essential Amino-Acid (TNAA). Among the Essential Amino Acids identified, arginine exhibited the mean value of 8.12±0.19g/100g Crude Protein, followed by Leucine (6.55±0.16)g/100g and Phenylalanine (6.45±0.19)g/100 Protein respectively. However, Lysine content of 4.61±0.08g/100g. Protein was lower than the recommended level of 5.50g/100g Protein. The Predicted Protein Efficiency Ratio (P-PER) of 1.45 suggests a good protein quality and digestibility. The Total Sulfur Amino Acid content of 4.50g/100g Crude Protein was within the recommended range. Compared to the conventional plant- protein sources,sour sop. Seeds exhibited a higher Total Essential Amino Acid content than soy bean meal (39.60g/100g), but lower than fish meal (57.60g/100g) Crude Protein. The Amino Acid profile of A. muricata (Sour Sop) seeds indicates their potential as a valuable protein sources for fish feed formulation, particularly when combine with other protein sources to complement the Amino Acid composition.